2015
DOI: 10.18805/ijar.7046
|View full text |Cite
|
Sign up to set email alerts
|

Determination of pre and post treatment oxidative status and oxidative DNA damage in diarrheic calves

Abstract: Increase in production of free radicals causes damage in lipids of cell membrane, weakening in functions of cell proteins and DNA damage. The aim of the present study was to determine the oxidative status, level of oxidative DNA damage and treatment effectiveness on these parameters on diarrheic calves. The study was conducted using 10 clinically holstein calves from 2-3 months of age. Antidiarrheic treatment containing Amonium sulphate (30mg/kg/day, Gabbrocol, Ceva Inc.), a mixture of Bismuth subcarbonate, ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…There was a significant increase in the total oxidant status andoxidative stress index in the calves affected with colibacillosis, however, there was significant decrease in total oxidant status. Our findings are in agreement with the study conducted by Kabu et al (2015). Similarly, many researchers also reported an increase in the values of TOS in many other diseases.…”
Section: A Study On Alteration In Serum Biochemical Parameters In Col...supporting
confidence: 93%
See 1 more Smart Citation
“…There was a significant increase in the total oxidant status andoxidative stress index in the calves affected with colibacillosis, however, there was significant decrease in total oxidant status. Our findings are in agreement with the study conducted by Kabu et al (2015). Similarly, many researchers also reported an increase in the values of TOS in many other diseases.…”
Section: A Study On Alteration In Serum Biochemical Parameters In Col...supporting
confidence: 93%
“…Aslan et al (2011) demonstrated that TOS levels were significantly higher in patients with ulcerative colitis while TAC was significantly lower. This rise of total oxidant status and decreased TAC appeared to be possibly associated with stress caused by the disease (Kabu et al, 2015).…”
Section: A Study On Alteration In Serum Biochemical Parameters In Col...mentioning
confidence: 90%
“…As a result, the oxidative stress index increased. In many studies, it has been reported that oxidative stress occurs in diarrhea and septicemia that develops as a result [39][40][41]. When cells are exposed to oxidative stress, they increase the activity and expression of antioxidant enzymes to protect them from damage caused by free radicals [42].…”
Section: Discussionmentioning
confidence: 99%
“…Free radicals are produced in the body as by products of normal metabolism and as a result of exposure to radiation and some environmental pollutants. Free radicals are normally neutralized by efficient systems in the body that include the antioxidant defense system (Kabu et al, 2015;Sardesai, 1995). Low levels of antioxidants in blood reflect oxidative damage caused by free radicals (Joreno, 1990;Kanbur et al, 2008;Noori et al, 2018).…”
Section: Introductionmentioning
confidence: 99%